Clinical and epidemiological characteristics of COVID positive pregnant women - Hospital Marino Molina Scippa 2020-2021 - León-Jacobo, Ruth (2023)
Introduction: The COVID-19 pandemic collapsed the health system, considered pregnant women as a vulnerable group and had a negative impact on access to health services, specifically prenatal care.Objective: To determine the clinical-epidemiological profile of pregnant women with COVID-19 infection treated at the Hospital Marino Molina Scippa between 2020 and 2021.Materials and Methods: Descriptive, retrospective and cross-sectional study in 298 pregnant women with a positive serological, antigen or PCR test, treated at the Gynecology and Obstetrics Service between 2020 and 2021. Medical records, birth book and epidemiological records were reviewed to collect sociodemographic variables, obstetric, epidemiological, clinical and newborn. The descriptive analysis was performed in SPSS v. 25.Results: The profile of the pregnant woman was an adult woman (64.8%), with a mean age of 31, secondary school (51.3%), cohabiting (72.8%), housewife (52.3%). , multigestation (35.9%) with 2.3 ± 1.3 pregnancies, uncontrolled (55.4%), without comorbidity (68.5%), 51.5% had normal delivery and newborn (NB) with normal Apgar (91.4%). The most frequent symptoms and signs were cough (11.9%), sore throat (9.8%), fever (7.4%), pharyngeal discharge (5.1%), and dyspnea (2.2%); 97.3% had the disease without complications. 47.3% were IgG reactive and 30.2% IgM IgG reactive, 78.2% did not know the contact person, of those who did, 32.3% indicated their husband and their home as the place of transmission (81.4%) or work (13.6%). Most of the NBs had no results, of those that did, 75.6% were IgG reactive and 13.5% IgG IgM reactive.Conclusions: The profile of the pregnant woman was adult, multigestational, uncontrolled, without comorbidity and the disease progressed without complications, 47.3% were diagnosed at a late stage (reactive IgG), the contact person was the husband and the place of transmission was his home. .